Secoisolariciresinol Diglucoside of Flaxseed and Its Metabolites: Biosynthesis and Potential for Nutraceuticals - Kezimana, Parfait; Dmitriev, Alexey A.; Kudryavtseva, Anna V.; Romanova, Elena V.; Melnikova, Nataliya V. (Frontiers in Genetics, 2018)
Secoisolariciresinol diglucoside (SDG), found mainly in flaxseed, is one of the essential lignans. SDG, as well as the beneficial fatty acid composition and high fiber content, has made flaxseed an important source of functional food or nutraceutical ingredients. Various studies have shown that SDG offers several health benefits, including protective effects against cardiovascular diseases, diabetes, cancer, and mental stress. These health benefits have been attributed to the antioxidant properties of SDG. Additionally, SDG metabolites, namely mammalian lignans, enterodiol and enterolactone, have shown promising effects against cancer. Therefore, understanding the biosynthetic pathway of SDG and its molecular mechanisms is a key to enable the production of new flaxseed cultivars rich in nutraceutical content. The present review highlights studies on the different health benefits of SDG, as well as lignan biosynthesis in flaxseed and genes involved in the biosynthetic pathway. Since SDG, the predominant lignan in flaxseed, is a glycosylated lignan, we also focus on studies investigating the genes involved in secoisolariciresinol glycosylation. These genes can be used to produce new cultivars with a novel level of glycosylation or lignan composition to maximize the yields of lignans with a therapeutic or protective potential.